Anti-angiogenic, antioxidant and xanthine oxidase inhibition activities of the mushroom Phellinus linteus - Song, YS; Kim, SH; Sa, JH; Jin, C; Lim, CJ; Park, EH (ELSEVIER SCI IRELAND LTD, 2003)
Fruiting bodies of Phellinus linteus were extracted with 70% ethanol at room temperature. The Phellinus linteus extract (PL) showed strong anti-angiogenic activity, which was detected using the chick embryo chorioallantoic membrane (CAM) assay. The in vitro antioxidant activities of PL were evaluated using two different bioassays. PL was comparable to Vitamin C in scavenging the stable free radical 1,1-diphenyl-2-picrylhyrazyl (DPPH). It also inhibited lipid peroxidation (LPO) in a concentration-dependent manner. These results suggest that antioxidant and anti-angiogenic activities of Phellinus linteus would be partly responsible for its anti-tumor effect. (C) 2003 Elsevier Ireland Ltd. All rights reserved.
Keywords: TUMOR-GROWTH; POLYSACCHARIDE